Trusted and anonymous authentication scheme for wireless networks - YANG Li1; MA Jian-feng 1; ZHU Jian-ming 2 (Tongxin xuebao)
A trusted and anonymous wireless authentication protocol was proposed by using of temporary identities and one time secret keys, both user identity and platform were authenticated under the proposed protocol.It has demonstrated that the proposed scheme is security and reliability, it can provide identity anonymity and platform anonymity, with domain separation property and key agreement process fairness, computation costs and turns of message exchange meet the demand for wireless IP networks security.